Komitmen, Kepuasan Kerja, Organizational Citizenship Behavior dan Kinerja Pegawai Kontrak - I Ketut Widiastra; Gede Sri Darma (Universitas Pendidikan Nasional, 2015)
In order to conduct the clean and good governance for excellent public services, theyhave to support with quality and profesionalism of human resources, responsibility, fair,honest, have a commitment, work satisfaction and loyalty. The purposes this research toexamine and analyze the influence of Commitment, work satisfaction, organizationalcitizenship behaviour (OCB) to contract workers performances.To examine the problem statements, spread the questionaries to 133 employes atDinas Pendapatan Bali Province. The data collected will analyze using structural equationmodelling (SEM). The results are fullfill GoodnessofFitIndexCriteria):Chi-square (c2 ) =107,246, Relatitive Chi-square (c2/df) = 1,192, Probability = 0,104, RMSEA=0,039, GFI =0,911, AGFI=0,866, TLI=0,981, CFI=0,986.The structural equation perform with the regression weight have 4 positives influenceand significance variables, there are committment to Organizational Citizenship Behavior(OCB), work satisfaction to Organizational Citizenship Behavior (OCB), work satisfaction tocontract workers performances, and organizational Citizenship Behavior (OCB) to contractworkers perfomances. Just one variable have negative value and significance, it iscommitment to contract workers performance. It's mean the committment is not affecteddirectly to contract workers performances, but through with Organizational CitizenshipBehavior (OCB). In other word, Organizational Citizenship Behavior (OCB) as interveningvariable between committmentandcontract workers performance.Theresearch contributions are measurement of employee performance at DinasPendapatan Bali Province are very important to do and the management give achievementsfor employee performance in obejectives and professional. This research also known thecommittment, work satisfaction and Organizational Citizenship Behavior (OCB) variableshave influences to employees performance. Cause of that, three variables must to continuedimplementation to achieved optimized and maximized value of employee performances andinline with management vision and purposess at Dinas Pendapatan Bali Province.Keyword : committment, work satisfaction, Organizational Citizenship Behavior (OCB),contract worker performances.